Encerrando almas bajo una sombra inesperada: Sistematización de la experiencia artístico-pedagógica en la ciudad de Cali – Valle del Cauca, en el curso danza Costa Pacífica periodo 2020-1 a inicios de la pandemia COVID-19. (2023)
This degree work seeks to base the process lived in the Experience Artistic-Pedagogical to the Current State of Tradition (EAPEAT) held in the city of Cali - Valle del Cauca, in the Pacific Coast dance subject period 2020-1, in the pandemic context COVID-19, with the purpose of creating a reflective memory of the experience lived by the master artists in training As well as leaving a precedent in the institution of that experience carried out in the framework of critical events for humanity.